Innovative Approaches to the Use of Digital Technologies in the Economy - Nishonkulov Shohruh Farxodjon ogli (Genius Publishing Group, 2021)
Article, scientifically studied role and importance of the use and importance of digital technologies in the modern economy. Scientific practical recommendations on the development of the management process and account in the activities of business entities were developed to improve electronic digital innovative technologies
Keywords: Information; digital economy; technology; improve